Vulnerability analysis of bridge superstructures under extreme fluid actions. (February 2020) - Greco, F.; Lonetti, P.; Nevone Blasi, P.
Abstract: Vulnerability analyses of bridge structures affected by extreme flood or tsunami wave loads in terms of loading variability and structural and fluid characteristics are conducted. The numerical model is developed by a combined three-dimensional (3D)/two-dimensional analysis based on phase field theory and 3D solid modeling of the fluid and structural systems, respectively. Coupling effects between the fluid and structure are simulated by using a moving mesh method based on an arbitrary Lagrangian–Eulerian approach to take bridge deformability and moving wall conditions into consideration. The proposed model is implemented in a finite element formulation, whose solution is achieved through a substructuring approach by introducing projection map operators defined to connect the structural and fluid systems. Several wave load scenarios related to the initial impact or dam break phenomena depending on inundation and blocking ratios and Froude numbers are considered. The main aim is to quantify the dynamic amplification effects of the kinematic and stress variables produced by the external loads with respect to conventional static analyses. In addition, the influences of bridge deformations on the hydrodynamic loads and vice versa are also discussed in terms of fluid and structural characteristics. Highlights: A combined FE 3D/2D model based on phase field, structural and ALE approaches is proposed. The effects of floods in terms of DAFs are investigated for several loading scenarios. Comparisons with experimental data and numerical results are proposed. Results show underestimations of the formulas proposed by existing design procedures.